Lectotypification of the names Plantago weldenii and P. commutata (Plantaginaceae) - Lazzaro, Lorenzo; Mugnai, Michele; Ferretti, Giulio; Lazzeri, Valerio; Bräuchler, Christian; Foggi, Bruno (Phytotaxa, 2020)
Genus Plantago (Plantaginaceae) hosts more than 200 species with complicated nomenclature and taxonomy. Within section Coronopus the two taxa Plantago weldenii and P. commutata have either been treated as different taxa or merged together. As a basis for a thorough taxonomic revision of these taxa, we designate here lectotypes for the two names P. weldenii and P. commutata, also discussing the main typification issues.